Analisis pengaruh PDRB dan jumlah penduduk terhadap Pendapatan Asli Daerah Kabupaten Kerinci - Afdhal Hendri Saldi; Zulgani Zulgani; Nurhayani Nurhayani (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
This study aims to analyze the effect of GRDP and population on Regional Original Income (PAD). The analytical method used is multiple linear regression with Ordinary Least Square (OLS) 2006-2020. The results of this study indicate that the development of Regional Original Income (PAD) in Kerinci Regency has increased except for 2009, 2012, 2017, and 2019 with an average PAD of Rp. Forty-seven thousand two hundred twenty million per year, the development of GRDP in Kerinci Regency has increased continuously except in 2008 with an average GRDP of Rp. 5,907.25 billion per year, and the average population growth in Kerinci Regency is 245,932 people per year. As well as the results of the analysis of factors that affect original regional income in Kerinci Regency, simultaneously the GRDP and population variables have a significant effect on Regional Original Income and partially GRDP is having a considerable impact number of residents has no substantial effect. Keywords: PDRB, Population, PAD